Into the Neuroscape: Perceptions of Pakistani Medical Students and Recent Graduates toward Neurosurgery - Shakir, Muhammad; Irshad, Hammad Atif; Shahzad, Akmal; Ali, Eisha Abid; Khowaja, Aly Hamza; Ahmer, Areesha; Enam, Syed Ather (Asian Journal of Neurosurgery, 2024)
Introduction Neurosurgery receives several applicants every year, but the decreasing size of the neurosurgery workforce in Pakistan despite evidence of initial student interest is perplexing. Therefore, it is vital to evaluate the perspective of medical students and recent graduates to get a holistic view of perceptions toward neurosurgery.Materials and Methods A nationwide cross-sectional study was conducted on a sample of medical students and recent graduates from different medical colleges. Their perceptions were gauged by multiple choice questions and barriers identified using Likert scale questions. Statistical analyses were carried out using the IBM Statistical Package for Social Sciences (SPSS) version 26.Results A total of 2,481 responses were recorded from study participants. Neurosciences and neurosurgery were a part of a medical school curriculum for the majority (64.9%) of the participants. However, a significant number (65.4%) of the participants do not have the opportunity to rotate in the field of neurosurgery. The respondents' perception of neurosurgery is shaped by various factors, such as university lectures (21.9%), digital media (16.7%), and social media (15.2%). Known patients (5.7%) and known neurosurgeons (4.8%) were considered the least influential sources. The top three characteristics associated with neurosurgery were consistent for both male and female students: difficult, interesting, and brain. Male respondents (25.22%) predominantly described neurosurgery as difficult, while female respondents (21.98%) found it interesting. Many females perceived neurosurgery as a male-dominated specialty, with 64% female participants agreeing with gender bias compared to 36% of males.Conclusion This study uncovers that medical students' views on neurosurgery are shaped by lectures, digital media, and social media, leading to preconceived ideas. These notions, including extended working hours, limited work–life balance, competition, gender bias, and stereotypes, impede their interest and comprehension of neurosurgery as a profession. To address this, students should have more opportunities to familiarize themselves with the field, allowing them to challenge these misconceptions and discover the captivating world of neurosurgery.
Keywords: image of a neurosurgeon; medical students' perspective; Pakistan; education; LMIC